Physical demands and movement characteristics of veterans football players - Egger, Florian; Graf, Vivian; Kotecha, Shaan; Saleh, Sohag; Meyer, Tim (Frontiers in Sports and Active Living, 2025)
BackgroundThis study aimed to investigate physical demands and movement characteristics of veterans football (VF) players. VF players were recruited from the West and South London Leagues.MethodsA 15 m shuttle run test was used to assess maximum heart rate (HRmax), and continuous heart rate was monitored to evaluate the cardiocirculatory strain during matches. Video analysis was performed to analyze movement characteristics, such as step counts, number of passes and sprints, changes of directions (COD), and standing time.ResultsA total of 91 male VF players (age, 45 ± 6 years; BMI, 26.3 ± 4.0 kg/m2) participated in the study. The mean heart rate was 147 ± 14 min−1 corresponding to 80 ± 8% of HRmax, with 57 ± 14% of match time completed above 80% HRmax. Midfielders completed more sprints (90 ± 10) compared with forwards (34 ± 6, p < 0.001) and defenders (50 ± 10, p < 0.01). Standing time was significantly higher (p < 0.001) in forwards (740 ± 87 s) and defenders (649 ± 111 s) than in midfielders (181 ± 17 s). During a match time of 86 ± 36 min, players covered 5,790 ± 963 steps, equivalent to approximately 6 km, and made 120 ± 59 COD and 128 ± 62 passes.DiscussionThe cardiocirculatory strain in VF football seems to be considerably high. Therefore, one VF match appears to be sufficient to meet the minimum of current guidelines on health-promoting activities. Position-specific differences in VF are evident for midfielders, who are potentially exposed to higher physical demands compared with other field positions.